INNOVATION ON LITERARY ASSESSMENT IN ARABIC LANGUAGE EDUCATION BOOK OF GRADE 7TH MUHAMMADIYAH MIDDLE SCHOOL - Labibah, Fitria Salwa; Baroroh, R. Umi; Alfarisi, Urfa Zuyina (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Literary assessment has undergone a significant transformation driven by advances in pedagogical strategies, technology integration, and its function, especially in Arabic language learning. To overcome the unique challenges and opportunities presented by the Arabic language and its rich literary heritage, researchers will explore innovations in literary assessment in Arabic language education books through the questions they contain as the object of this analysis-based research. The discussion will focus on transitioning from conventional assessment techniques to a more dynamic, critical, and varied basis. This research is a type of qualitative research, namely library research. The analysis technique used is content analysis. This technique is used to compile discussions and patterns on primary data based on secondary data that has been collected. This research aims to explore the extent to which students' critical thinking skills can be measured through literary assessments that are tested in the form of essay questions. Thus, the results of this study show that literary assessment based on critical thinking not only improves the quality of literary learning evaluation but also provides students with the opportunity to develop more in-depth critical thinking skills. From this renewal, it is hoped that students' critical skills can be trained to improve literary skills in learning Arabic through literary assessment innovations developed by researchers.